Geology along the Arniko Highway between Barabise and Kodari (China-Nepal Boarder) area, central Himalaya (Journal of Nepal Geological Society, 2011)
The area between Barabise and Kodari in central Nepal along the Arniko Highway is geologically located into Higher Himalayan Crystallines (HHC) and Lesser Himalayan Sequence (LHS) that is separated by the Main Central Thrust (MCT). The HHC consists of amphibolite facies rocks (pelitic schist, psamitic schist, pelitic gneiss and quartzite), while LHS is comprised by green schist to amphibolite facies rocks (phyllite, calcareous phyllite, garnet-mica schist, black schist, quartzite and augen gneiss) in uppermost section and carbonate (dolomite and limestone) with phyllite, and metasandstone in lower section. The MCT in the area is oriented in E-W direction with about 30° dip due north and S-C structure preserved in augen gneiss of LHS characterizes the top-to-south sense of shearing, which could be related to the movement along the MCT. Mineral lineation marked by stretched mica indicates N to NNE direction in both HHC and LHS.Metamorphism of inverse grade from biotite at stratigraphically lower most section of Kuncha Formation to garnet at the uppermost section having schist and augen gneiss is obvious close to the MCT in the section. However, the Kuncha Formation contains tiny crystals of garnet in the rocks of greenschist facies. Kyanite and sillimanite isograds are developed in pelitic and psamitic schists, and pelitic schists appeared at the basal part of HHC above the MCT. The transformation of garnet to chlorite at the margin and fractures and formation of chlorite within bulk rocks of the MCT zone and HHC are the indicators of traces of retrograde metamorphism because of dropping in pressure-temperature probably related to post deformation event.